Response differences of gut microbiota in oligofructose and inulin are determined by the initial gut Bacteroides/Bifidobacterium ratios - Yin, Pingping; Du, Ting; Yi, Shanrong; Zhang, Chengcheng; Yu, Leilei; Tian, Fengwei; Chen, Wei; Zhai, Qixiao (Food research international, 2023)
[Display omitted] •FOS was slightly better than inulin in modulating the gut microbiota.•H was enriched for butyrate-producing bacteria and butyric acid after FOS intervention.•After inulin intervention, the L was enriched with more glycolytic functions.•H was enriched for amino acids and aminoglycolytic functions after inulin intervention. Prebiotics are known to modulate the gut microbiota, but there is host variability, mainly due to differences in carbohydrate-utilisation by gut microbiota. Bifidobacterium and Bacteroides are powerful carbohydrate-utilising bacteria, and the ratio of both is closely related to the utilisation of prebiotics. However, the differential impact of prebiotics on the composition and function of the gut microbiota and its metabolites in participants with different Bacteroides/Bifidobacterium (Ba/Bi) ratios have not been studied. Here, we conducted a 4-week randomised double-blind, parallel four-arm trial using two prebiotics (oligofructose and inulin) in two populations with high Ba/Bi (H) and low Ba/Bi (L). The response to prebiotics in both populations was influenced by the baseline microbiota background specificity. Notably, at an overall level, FOS was slightly better than inulin in modulating the gut microbiota. Difference in gut microbiota regulation by FOS across microbiota contexts were significant between the two groups. Butyric acid-producing bacteria were significantly more abundant in H and further elevated butyric acid and related metabolite levels, with H more likely to benefit from the FOS intervention. The two groups showed only metabolic differences in their response to inulin, with L showing a significant increase in propionic acid and being enriched in glycolysis functions, whereas H was enriched in amino acids and aminoglycolysis functions. Overall, these results provide a basis for selecting appropriate prebiotics for participants with different gut backgrounds.